The Effect of Enzymatic Hydrolysis on The Properties of Protein Hydrolysate from Paddy Mushroom - Palupi, Niken Widya; Windrati, Wiwik Siti; Tamtarini, Tamtarini (UI Scholars Hub, 2010)
Protein hydrolysate was prepared from Paddy (Volvariella volvaceae) mushroom. Hydrolysis uses commercially protease available Protamex ™ with enzyme concentration of 0.1% (w/w). Hydrolysis was performed at three different temperatures (room temperature, 40 °C, and 50 °C) with different incubation periods (60, 90, and 120 minutes). Enzyme inactivation was done in 90 °C for 3 minutes. Yield and degree of hydrolysis ranged from 94.76% to 99.55% and 19.06% to 24.59%. Protein solubility was about 89–11,8%. The longer time of hydrolysis, the darker the color of protein hydrolysate. Protein hydrolysate which has hydrolysis at 50 °C for 120 minutes has the highest protein yield and the best sensory properties: 4.76 (taste liking), 3.68 (aroma liking), and 4.56 (overall liking). However, this protein hydrolysate has the potential for application as an ingredient in formulated diets.